Applying the Theory of Cultural Production: Authorship in the Literary Communities of Yogyakarta, Indonesia - Suharmono, Suharmono (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2022)
Since the fall of the New Order in 1998, which began an era of political reform in which freedom of speech and association were guaranteed, literary communities have mushroomed in Indonesia; Yogyakarta is no exception. This city, through its literary communities, has played an important role in the development of Indonesian literature. Employing a Bourdieuan perspective, in which authors are understood as emerging within the field of cultural production, this paper explores the phenomenon of authorship in the literary communities of Yogyakarta. It finds that the field of cultural production in Yogyakarta has been influenced by the existence of literary communities, including the rise of new writers within said communities.